QUALITY OF WORK LIFE IN A HIGH SCHOOL IN THE STATE OF AMAZONAS/BRAZIL - Soares, Jackson Carvalho; Coelho, Moisés Andrade (Brazilian Journal of Production Engineering, 2019)
This research aims to apply a model to evaluate the quality of work life in a public high school in the municipality of Itacoatiara/AM. As for the approach used in the study, it is quantitative and from the point of view of the objectives, it is characterized as exploratory. With respect to technical procedures, it is configured as a case study. The delimitation of the universe was composed of a public high school located in the municipality of Itacoatiara/AM and as research techniques were used: (1) indirect documentation through documentary research and bibliographic research and (2) extensive direct observation by through questionnaires. The study showed that aspects related to the work environment and infrastructure negatively affect teachers, but teachers have good relationships with other colleagues and students, that is, work has a positive impact on teachers’ lives, besides pointing to a level of satisfactory stress, however very close to unsatisfactory levels among teachers.